(untitled) (University of Khartoum Journal of Agricultural Sciences, 2025)
Selection of optimum tillage systems can reduce the cost ofland preparation and maintain or increase crop yields. The present studywas carried out on a heavy clay soil in the New Halfa agricultural schemeto compare and evaluate the costs of some land preparation tillagetreatments for cotton production. Five tillage treatments (disc ploughing,chisel ploughing, ridging, disc harrowing and no-tillage) were used in arandomized complete block design. Data on soil, crop, machinery andland preparation costs were collected. Significant differences (P = 0.01)between the effect of tillage implements on the measured machineryparameters were obtained. Although the conventional tillage treatments(disc ploughing and chisel ploughing) resulted in significantly higheryields than the conservational tillage treatments (ridging, disc harrowingand no-till), they were more expensive and time and fuel consuming.